(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
In acute experiments on intact spinal rats with beforehand chronical venom intoxication and cool-hardening the influence of armenian adder (Vipera raddei) venom on the basic and evoked (stimulation of n. ischiadicus) electrical activity of single intemeurones of lumbo-sacral area (U-VI lamines at Rexed) of spinal cord was investigated. The statistical analyses on-line was done. At rats with chronical intoxication and cool-hardening only pronounced simplification of activity in the beginning was revealed.